Entre pierres et bétons, routes de montagne et transitions écologiques du tourisme, l’exemple du Vercors (1870-2023) - Emma-Sophie Mouret (Mondes du Tourisme)
This article examines the role of mountain roads in the ecological transition of the tourism sector. Based on a territorial research approach developed on the Vercors massif (France), this study examines the long-term links between tourism, roads, and the environment. Since the 1960s, the Vercors massif has seen various forms of tourism develop. These have been linked to the different vocations assigned to mountain areas and to changes in global sensitivities. Over the years, it has been common for tourist uses to clash with each other, with the roads playing a central role in these tensions. Today, fragile balances are threatened by the urgency that accompanies the notion of transition.